A comparative performance study of distributed mutual exclusion algorithms with a class of extended Petri nets - Kostin, A; Ilushechkina, L; Basri, E (Springer-Verlag Berlin, 2005)
A few algorithms of distributed mutual exclusion are discussed, their unified model in terms of a finite-population queuing system is proposed, and their simulation performance study is presented with the assumption that they use multicast communication if possible. To formally represent the algorithms for simulation, a class of extended Petri nets is used. The simulation was done in the simulation system Winsim based on this class of Petri nets.
6th International Conference on Algorithms and Architectures for Parallel Processing -- OCT 02-03, 2005 -- Melbourne, AUSTRALIA
Keywords: Information-Structure; Efficient